2019
DOI: 10.1002/qua.26032
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus mononitride: A difficult case for theory

Abstract: Phosphorus nitride (PN) is the simplest molecule formed solely by phosphorus and nitrogen. It represents an interesting model for materials, where phosphorus is directly attached to nitrogen. Nevertheless, both theoretical and experimental studies often provide an incomplete picture on the structural, electronic, and spectral properties of PN. Theoretical predictions often suffer from insufficient level of theory, incomplete basis set, or from neglecting several effects, for example, zero‐point vibrational cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…For the subset of heteronuclei, we found that the PN molecule dominated the deviations of the LHs and for that matter any hybrid functional with larger exact-exchange admixtures , (TPSSh has only 10% and is thus somewhat less sensitive). This reflects the particularly large static correlation effects of this diatomic molecule . Our statistical evaluations in Figure thus provide results with PN either excluded (solid bars) or included (hatched bars).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For the subset of heteronuclei, we found that the PN molecule dominated the deviations of the LHs and for that matter any hybrid functional with larger exact-exchange admixtures , (TPSSh has only 10% and is thus somewhat less sensitive). This reflects the particularly large static correlation effects of this diatomic molecule . Our statistical evaluations in Figure thus provide results with PN either excluded (solid bars) or included (hatched bars).…”
Section: Resultsmentioning
confidence: 92%
“…This reflects the particularly large static correlation effects of this diatomic molecule. 61 Our statistical evaluations in Figure 1 thus provide results with PN either excluded (solid bars) or included (hatched bars). For comparison, we give also the data for the first generation uncalibrated LHs (including LH07s-SVWN, which is based on an s-LMF) and TPSSh.…”
Section: Resultsmentioning
confidence: 98%
“…This makes a theory-against-theory comparison preferable, provided a benchmark level with sufficiently high accuracy is available. For main-group nuclear shieldings, a number of high-level benchmarks have been put forward, typically based on CCSD­(T) “gold standard” data for small molecules. ,,, However, these data sets usually have been based on a relatively small number of values for a given nucleus, and the different sets often used different basis sets, which may lead to variable accuracy. We therefore decided to construct a larger benchmark set of light main-group nuclear shieldings at a uniform computational level to be used in validation studies of more approximate methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a benchmark study, a fairly good performance of B3LYP among over 40 other density functionals in predicting gas‐phase shieldings of nine small molecules in the complete basis set limit was observed . Recently, we also published several studies using B3LYP functional for prediction of NMR parameters in some small and middle‐size molecules . However, one should be aware that in case of some “exotic” molecular systems, B3LYP‐predicted chemical shifts and coupling constants could be less accurate …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we also published several studies using B3LYP functional for prediction of NMR parameters in some small and middle‐size molecules . However, one should be aware that in case of some “exotic” molecular systems, B3LYP‐predicted chemical shifts and coupling constants could be less accurate …”
Section: Introductionmentioning
confidence: 99%